Netnografi: Perspektif Netizen Terhadap Kenaikan Tarif PPN 11% - Moh. Faisol; Norsain Norsain (Universitas Muhammadiyah Malang, 2023)
Purpose: The purpose of this study was to determine netizens' perceptions of the 11% increase in the VAT rate. Methodology/Approach: The researcher uses a qualitative approach using the netnographic method because it is relevant to the discussion of netizen responses originating from social media. Research data collection used observation and documentation on the twitter account (#PPNNAIK) with the NCapture for Nvivo application, then analyzed using qualitative data analysis and NVivo R1 software. Findings: The results of this study state that there are pros and cons related to the 11% VAT increase policy that must be understood broadly and fundamentally so that it is wiser to react to it and does not cause speculation in the community. Those who are against say that an 11% VAT increase along with an increase in the prices of other necessities amid the COVID-19 pandemic is inappropriate because it will burden the people in meeting their daily needs. Meanwhile, those who are pro argue that the goods/services that are subject to 11% VAT are not goods/services that are basic needs of the community, such as rice, sugar, and the like, which are consumed by the lower middle class. However, the increase in the imposition of taxes on goods consumed by the upper middle class, so that the 11% increase in VAT has proven to increase state revenues and return to the community. Practical and Theoretical contribution/Originality: The implication of this research is that it is important for the public to understand each